The indiscrete image: infinitude and creation of the human - Alvis, Jason W. (The journal for cultural and religious theory, 2013)
A review essay of Thomas Carlson’s The Indiscrete Image: Infinitude and Creation of the Human, 2008 Chicago: University of Chicago Press. xi + 236 pp. ISBN: 978-0226093154